2019
DOI: 10.1093/mmy/myz009
|View full text |Cite
|
Sign up to set email alerts
|

β-citronellol alters cell surface properties of Candida albicans to influence pathogenicity related traits

Abstract: The pathogenicity of Candida albicans, an opportunistic human fungal pathogen, is attributed to several virulence factors. β-citronellol is a monoterpenoid present in several plant essential oils. The present study explores the antifungal potential and mode of action of β-citronellol against C. albicans ATCC 90028 (standard), C. albicans D-27 (FLC-sensitive), and C. albicans S-1 (FLC-resistant). Anti-Candida potential was studied by performing MIC, MFC, growth curves, disc diffusion, spot assay, and WST1 cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Of the monoterpenes 1,8-cineole and αpinene from rosemary oil, α-pinene proved to be a very active compound, while 1,8-cineole has lower antifungal activity [53]. Additionally, the monoterpenoid β-citronellol decreases the hydrolytic enzymes secretion in C. albicans [54], consistent with the strong inhibition of phospholipase by rosemary oil in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Of the monoterpenes 1,8-cineole and αpinene from rosemary oil, α-pinene proved to be a very active compound, while 1,8-cineole has lower antifungal activity [53]. Additionally, the monoterpenoid β-citronellol decreases the hydrolytic enzymes secretion in C. albicans [54], consistent with the strong inhibition of phospholipase by rosemary oil in our study.…”
Section: Discussionsupporting
confidence: 87%
“…For CitO, its antifungal activity was notably linked to the disruption of the cell membrane, followed by the leakage of cell constituents [19]. Cell disruption seems to be related to a modification of ergosterol content and production [20,21]. Lim and Shin [22] demonstrated that the effects of CitO on the membrane are not only due to the impairment of ergosterol biosynthesis, but also to a change in the lipid composition of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol is a phenolic monoterpene and its antibacterial effect has been demonstrated against various bacterial species [ 18 ], [ 19 ], [ 20 ], [ 21 ]. Alpha-terpinol also has an antibacterial effect [ 22 ]. A recent study has reported that beta-citronellol has anti-fungal activity against Candida al bi ca ns [ 23 ].…”
Section: Discussionmentioning
confidence: 99%